Endogenous perception and peasant strategies of adaptation to climate variabilities and changes in the municipality of Zagnanado in Southern Bénin - ADJAHOSSOU, Vidédji naéssé; ADJAHOSSOU, BAÏ SÈDAMI; DJEGO, JULIEN GAUDENCE MAHUTIN; VISSIN, EXPÉDIT WILFRID (My University, 2021)
Peasants of the municipality of Zagnanado have socio-anthropological data used to determine seasons. Those data are confronted with the phenomenon of climate change. The objective of the study was to have a better knowledge of the use of phytoclimatic indicators in the municipality of Zagnanado. The methodological approach was consisted in interviewing target populations, field visits and the analysis of rainfall trends. Based on surveys of 119 peasants, the results of the investigations showed that the populations of the municipality of Zagnanado had knowledge on the climatic facts. Observation of the phenology of natural vegetation allowed the population to predict the seasons. For about 50% of the interviewed people, the flowering of Ricinodendron heudelotii and Parkia biglobosa was seen as a warning of the arrival of the rainy season. Similarly, the flowering of Glyphaea brevis and Vernonia amygdalina announced the dry season according to 86% of the interviewed people. However, climate change was shaking up these phytoclimatic indicators, as shown by the analysis of rainfall and temperature over the period 1960 to 2008. In response to these current climate variabilities and changes, peasants of the municipality of Zagnanado have developed adaptation strategies. including changing the agricultural calendar
Keywords: Climate variability; Phytoclimatic indicators; Peasant strategies